The Road to Recovery #6: Evaluating Virtual Strategies to Build Community Capacity and Resilience - Cody Ross Gusto; Colby Silvert; John Diaz; Glenn Israel (EDIS, 2021)
This sixth publication in the Road to Recovery series provides tips and strategies for Extension professionals interested in evaluating efforts to promote community capacity building and community resilience using virtual platforms. This new 5-page publication of the UF/IFAS Department of Agricultural Education and Communication was written by Cody Gusto, Colby Silvert, John Diaz, and Glenn Israel. https://edis.ifas.ufl.edu/wc385